The Impact of Good Corporate Governance on the Quality of Sustainability Reports - Maria M. Virginia De Pazzi; Putu Agus Ardiana (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This research aims to examine the effect of Good Corporate Governance (GCG) on the quality of Sustainability Reports (SR). The population for this study consists of energy companies listed on the Indonesia Stock Exchange (IDX) in 2023. The sample was determined using purposive sampling, resulting in a total of 143 companies. Legitimacy theory is used to explain the findings. Data analysis was performed using multiple linear regression. The results show that the proportion of independent commissioners, the frequency of audit committee meetings, and the proportion of managerial ownership positively affect the quality of SR. Conversely, the size of the board of directors negatively affects the quality of SR. Keywords: Sustainability report quality; proportion of independent commissioner; audit committee meetings; proportion of managerial ownership; board size.